The relationship between psychological stress, salivary cortisol levels, and psoriasis severity - Nyoman Suryawati; Ketut Kwartantaya Winaya; I Gusti Ayu Agung Praharsini; I Nyoman Wande (Indonesian Journal of Biomedicine and Clinical Sciences, 2026)
Psychological stress has been associated with psoriasis, possibly through neuroendocrine pathways involving the hypothalamic-pituitary-adrenal axis. However, evidence on salivary cortisol levels in psoriasis vulgaris remains inconsistent, and data from Indonesian populations remain limited. This analytical cross-sectional study was conducted at Ngoerah Hospital, Bali, Indonesia, from July to October 2024. The study included 44 patients with psoriasis vulgaris and 41 non-psoriasis controls. Psychological stress was assessed using the Perceived Stress Scale; psoriasis severity was evaluated using the Psoriasis Area and Severity Index; and salivary cortisol levels were measured using an enzyme-linked immunosorbent assay. Between-group comparisons and correlation analyses were performed to evaluate the relationship between psychological stress, salivary cortisol levels, and psoriasis severity. Psychological stress scores and salivary cortisol levels did not differ significantly between the psoriasis and non-psoriasis groups. In the psoriasis group, salivary cortisol levels were not correlated with psychological stress. However, salivary cortisol levels showed a weak negative correlation with psoriasis severity, as measured by the PASI score (r=-0.33; p=0.03). This study found no significant correlation between salivary cortisol levels and psychological stress, but revealed a weak negative correlation between salivary cortisol levels and psoriasis severity.